Progression of Alzheimer Disease in Europe: data from the European ICTUS study - Vellas, Bruno; Frölich, Lutz (Current Alzheimer research, 2012)
The clinical progression of Alzheimer disease (AD) was studied in European subjects under treatment with AChE inhibitors (AChE-I) in relation to geographical location over a 2-years period. One thousand three hundred and six subjects from 11 European countries were clustered into 3 regions (North, South, West) and investigated with biannual follow-up over 2 years. Primary outcomes were cognitive, functional and behavioral measures. Caregiver burden, hospital admission and admission to nursing home were also recorded. Participant cognitive function declined non-linearly over time (MMSE: -1.5 pts/first year, -2.5 pts/second year; ADAScog: + 3.5 pts/first year, + 4.8 pts/second year), while the progression of behavioral disturbances (NPI scale) was linear. Neither scale showed regional differences, and progression of the disease was similar across Europe despite different health care systems. Functional decline (ADL, IADL) tended to progress more rapidly in Southern Europe (p=0.09), while progression of caregiver burden (Zarit Burden Interview) was most rapid in Northern Europe (5.6 pts/y, p=0.04). Incidences of hospital admission (10.44, 95%CI: 8.13-12.75, p<0.001) and admission to nursing home (2.97, 95%CI: 1.83-4.11, p<0.001) were lowest in Southern Europe. In general cognitive and functional decline was slower than in former cohorts. European geographical location reflecting differences in culture and in health care system does not impact on the progression of AD but does influence the management of AD subjects and caregiver burden.